(untitled) (Eurasian Medical Research Periodical, 2023)
The increasing demand for the products of rabbit breeding requires the study of the body as a whole and its individual systems important for life activity, including the respiratory organs, which to date remain unstudied. This work is devoted to the elucidation of peculiarities of the structure of the lungs of the domestic rabbit (Oructolagus). By methods of dissection and morphometry the structure of lungs was studied and their belonging to a certain comparative-anatomic type was determined. As a result of the study the lung lobe structure in the domestic rabbit was established, their topography, shape, sizes, mass, coefficient of asymmetry by mass were determined